PENGARUH PENDIDIKAN KESEHATAN BERBASIS MULTIMEDIA TERHADAP PENINGKATAN PENGETAHUAN DAN PERAN AYAH DALAM PEMBERIAN ASI - Nina Nirmaya Mariani; Suratmi Suratmi (JURNAL MEDIA KESEHATAN, 2022)
Background: Mother Breastfeeding is ideal for baby food as it provides essential nutrients for growth and development. Many factors influence the failure of breastfeeding. The lack of knowledge and support of those around the mother, namely the father/husband. One way to increase knowledge and roles is by providing health education using multimedia (video), where videos are more effective in improving breastfeeding abilities. It is hoped that breastfeeding fathers can increase knowledge and increase their role in the success of breastfeeding with this media. Objectives: To find out the effect of multimedia-based health education on increasing knowledge and the role of fathers in breastfeeding at PMB Eliyanti, S.Tr.Keb District of Kuningan. Methods: The type of research used is quasi-experimental research with one group pre and post-test design. The number of samples using the formula with the sample size is 30 people. Sampling with Systematic Random Sampling technique. Statistical tests were used to determine the increase in knowledge using Wilcoxon while the role of fathers used paired t-test. Results: This shows the knowledge variable the median value of the pre-test is 21 and the post-test is 24 with a p-value of 0.000 while the father's role variable has an average pre-test value of 65.50 with a standard deviation of 1.021 and the average knowledge in the post-test is 72. .90 with a standard deviation of 0.57 and a p-value of 0.000. This shows that there is an effect of multimedia-based health education on knowledge of breastfeeding and the role of fathers in breastfeeding. Conclusion: Multimedia health education affects the increase in knowledge about breastfeeding and the role of fathers in breastfeeding Keywords: Health education, multimedia, knowledge, father's role, breastfeeding.